PENGEMBANGAN AGROFORESTRY MELALUI PELATIHAN PEMBUATAN MIKROORGANISME LOKAL DAN ECO ENZYM MENDUKUNG PERTANIAN BERKELANJUTAN KEPADA PETANI HUTAN DESA TAMBAKSARI PURWODADI PASURUAN - Mamilianti, Wenny; Habibi, Muhammad Afryzal; Munawaroh, Azkiyatul; Hamdani, Mohammad; Qoyum, Nyla; Ningsih, Nofita; Hadi, Muhammad Sofiyan; Mufsida, Siska Amelia Tafsilatul; Habibi, Muhahhad Afryzal; Rizqi, Muhammad Faris; Wibisono, Agung; Ubaidillah, Akhmad Roychan (Universitas Mataram, 2025)
Tambaksari village's natural resources, such as coffee plants, other forest plants, bananas, and spices, provide benefits for agricultural sustainability and forest preservation. The existing livestock potential also benefits plant growth. However, farmers' knowledge and skills in making and utilizing these resources are still lacking, as evidenced by the underutilization of livestock manure and the resulting pollution. The purpose of this community service is to improve the knowledge and skills of forest farmers in making biocomposers from local resources. The methods used are training, demonstration/practice, mentoring, and activity evaluation. The results of the activity show an increase in participants' knowledge and skills in making biocomposers. The increase in knowledge and skills was 77% for MOL production and 87% for eco-enzyme production. During the mentoring stage, participants responded that 100% of participants responded that they were willing to apply the technology provided in the training. The training on making MOL and eco-enzyme for Tambaksari village forest farmers increased their knowledge and skills in making MOL and Eco-enzyme.